Analisis Kinerja Wireless Access Point Menggunakan Wifi Monitoring Tools Berbasis Raspberry Pi 3 - Ganner Antero; Abdul Rasyid; Martono Dwi Atmadja (Jurnal Jaringan Telekomunikasi, 2021)
Mini computers are now advanced enough to be used in various fields. One of the mini computers that used is the Raspberry Pi 3. The Raspberry Pi 3 is a mini computer that has a feature for a wireless LAN. The wireless LAN feature on a mini computer can be used as a Wireless Access Point. The Raspberry Pi 3 can be an alternative to Wireless Access Point. However, mini computers have different capabilities with Wireless Access Points in general because they have different specifications. The purpose of this study was to determine the performance of the Raspberry Pi 3 based Wireless Access Point. The Raspberry Pi 3 is connected to a laptop that already connected to the internet via a LAN cable . Raspberry Pi 3 is configured as a Wireless Access Point (WAP) and programmed for data retrieval and monitoring in the form of traffic and user information displayed in a web display. In this study, the Raspberry Pi 3 was tested as a Wireless Access Point. The ability of the Raspberry Pi 3 as a Wireless Access Point is greatly influenced by the traffic carried out by the user. According to the test results, the Raspberry Pi 3 as a Wireless Access Point has a maximum limit of 13 users with high traffic loads, 17 users with medium loads and 27 with low loads. This shows that the Raspberry Pi 3 is worthy of being used as a Wireless Access point on a small scale.